2021
DOI: 10.1016/j.redox.2021.101936
|View full text |Cite
|
Sign up to set email alerts
|

MitoQ protects against hyperpermeability of endothelium barrier in acute lung injury via a Nrf2-dependent mechanism

Abstract: Recently, numerous evidence has revealed that excessive reactive oxygen species (ROS) production and mitochondrial disruption during acute lung injury (ALI) and its most severe form, acute respiratory distress syndrome (ARDS) will aggravate the inflammatory process. To identify whether antioxidation can be one of the treatment strategies during this progress, we chose mitoQ, a mitochondria-targeted antioxidant that was proved to be effective in reducing ROS generated in mitochondria, as a ROS scavenger to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 48 publications
(32 reference statements)
3
52
0
Order By: Relevance
“…These are generally purposely synthesized for targeting mitochondria. One well-known compound is mitoQ that has been investigated in a variety of diseases including kidney disease [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. Using type 1 diabetic Akita mouse model, Chacko et al [ 163 ] demonstrated that mitoQ administration over a 12-week period improved tubular and glomerular function in the Akita diabetic mice and decreased urinary albumin content to the level as observed in healthy controls.…”
Section: Therapeutic Approaches To Counteracting Dkdmentioning
confidence: 99%
“…These are generally purposely synthesized for targeting mitochondria. One well-known compound is mitoQ that has been investigated in a variety of diseases including kidney disease [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. Using type 1 diabetic Akita mouse model, Chacko et al [ 163 ] demonstrated that mitoQ administration over a 12-week period improved tubular and glomerular function in the Akita diabetic mice and decreased urinary albumin content to the level as observed in healthy controls.…”
Section: Therapeutic Approaches To Counteracting Dkdmentioning
confidence: 99%
“…Nrf2 is a pleiotropic transcription factor through antioxidant response elements within the regulatory region of many target genes such as HO-1 and NQO1, coordinates antioxidative allowing all types of cells adapt to detrimental conditions caused by intracellular or extracellular stress [28,31]. In this study, we found that DMF obviously promoted the expression of Nrf2 and inhibited the production of ROS in LPSinduced BEAS-2B cells.…”
Section: Discussionmentioning
confidence: 58%
“…Acute injury includes myocardial, cerebral, renal, and hepatic ischemia-reperfusion injury (IRI) [ 1 , 2 ]. Acute organ injury is characterized by potent proinflammatory responses involving leukocyte migration, cytokine release, microvascular thromboses, and cell death [ 3 – 5 ]. The proinflammatory phase of acute injury-associated systemic immune responses is often followed by an immunosuppressive phase [ 6 ].…”
Section: Introductionmentioning
confidence: 99%